Hal-Hal Yang Ada Hubungan Dengan Serangan Asma Atopik Pada Penderita Anak Di Berbagai Lokasi Di Dunia Periode Tahun 1998 Sampai Dengan Tahun 2019 - Akbar, Moh.Fahmi; Hardjo, Marhaen; Rahmadani, Annisa Rahmadani (Bosowa Medical Journal, 2024)
An atopic asthma attack is an episode of progressive increase (worsening) of symptoms of cough, shortness of breath, wheezing, chest tightness, or any combination of these symptoms as a result of an exaggerated immune response or hypersensitivity reaction involving an allergic response that produces antibodies. IgE specific to antigen. This study aims to determine the things that have a relationship with atopic asthma attacks. This research is a systematic review research by processing the results obtained from ten scientific research journals with a case control research design. Based on ten studies analyzed, it shows that there are things that have a relationship with atopic asthma attacks in pediatric patients in various locations in the world, namely there is a significant relationship between atopy history, house dust mites, weather changes, pollutants, and pollen on atopic asthma attacks with p value < 0.01. Meanwhile, there is no significant relationship between pet factors and atopic asthma attacks with p value > 0.01.: Based on this study, it is known that things that have a relationship with atopic asthma attacks in pediatric patients in various locations in the world from 1998 to 2019 are a history of atopy, house dust mites, weather changes, pollutants, and pollen.